Análise da vida útil residual de estrutura de concreto armado - Leal, Rafael Lanzarini (Universidade do Vale do Rio dos Sinos, 2019)
The concrete, one of the most consumed products in the world, has excellent characteristics to support compressive stresses, and when combined with steel also presents high tensile strength, receiving the name of reinforced concrete. The steel bars added to it are passivated due to the high alkalinity of the concrete, providing protection against reinforcement corrosion. The carbon dioxide present in the atmosphere with the presence of moisture reacts with the alkaline hydroxides present in the concrete microstructure, forming calcium carbonate and consequently decreasing the pH of the structure, leaving the reinforcement susceptible to corrosion. This work aims to analyze the residual useful life of a reinforced concrete structure of a residential building dating from the 70s, inserted in an urban environment, in the city of Novo Hamburgo-RS, facing the advancement of the carbonation front. For the analysis, dust from holes drilled in 8 points of the structure on the ground floor was extracted, being three points located on the outside of the building, and another five points located in the garage of the building. The analysis was performed by spraying phenolphthalein chemical reagent on the dust collected through the holes and thus identifying the carbonated front thickness, applying the Tuutti square root time formula, thus stipulating the residual useful life of the structure. The results obtained with the analysis showed that in five points analyzed the structure exceeded the design life stipulated by the current reinforced concrete standard, NBR 6118: 2014 and three other points ahead carbonation found the steel bars of the structure.
Keywords: Frente de carbonatação; Vida útil residual; Patologia de construções; Carbonation front; Residual life; Pathology of buildings